Real-Time Optical-Wireless Video Surveillance System for High Visual-Fidelity Underwater Monitoring - Meiwei Kong (IEEE Photonics Journal, 2022)
Real-time, dynamic, and visual monitoring of underwater scenes would become an important research topic with the development of underwater wireless optical communication (UWOC), autonomous underwater vehicle, and video fusion technologies. To this end, we developed a UWOC-based 2K real-time digital video surveillance prototype named AquaF-seer. Using a light-emitting diode and an avalanche photodetector based diffused line-of-sight UWOC system, real-time video transmission with a high resolution of 1920 × 1080 pixels is achieved over various channels, i.e., 1.5-m free space channel, pure water channel, pure water channel with 1.53-mL/s bubble-induced turbulence, pure water channel with 42.40-mL/s bubble-induced turbulence, simulated pure sea water channel, and coastal ocean water channel. Moreover, 46-m and 5-m video monitoring are implemented in free space and an outdoor diving pool. It indicates the reliability of the prototype, which is the first step to realize underwater visual monitoring in future human-robot interaction applications.